Mediating effect of psychological process variables on the relationship between dysfunctional coping and psychopathologies: a comparative study on psychopathologies during COVID-19 - Nurfarah Lydia Hambali; Friska Ayu; Pang, Nicholas Tze Ping; Mohd Amiruddin Mohd Kassim; Hafid Algristian; Moch. Sahri; Nelbon Giloi; Syed Sharizman Syed Abdul Rahim; Azizan Omar; Mohammad Saffree Jeffree; Walton Wider (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The COVID-19 crisis has had repercussions on global mental wellbeing. This study aimed: (1) to identify the mediating role of psychological process variables, namely psychological mindedness, psychological mindfulness, and psychological inflexibility on the relationship between dysfunctional coping and psychopathologies in Indonesian undergraduate students subjected to national quarantine orders throughout July, 2020 and (2) to compare the level of anxiety, depression, and anxiety between Indonesian and Malaysian undergraduate students. A cross-sectional study was performed with 869 Indonesian undergraduate students from Nahdlatul Ulama University of Surabaya (UNUSA) and 515 undergraduate students from Universiti Malaysia Sabah (UMS). The BIPM, MAAS, AAQ-I, DASS-21, and Brief COPE were used to assess the research variables. The proportion who scored “moderate” and above for depression, anxiety, and stress were 20.2%, 25.0%, and 14.2%, respectively, in Malaysian samples and 22.2%, 35.0%, and 23.48% in Indonesian samples. In Study 1, psychological mindedness, psychological mindfulness, and psychological inflexibility significantly mediated the relationship between dysfunctional coping and psychopathologies. In Study 2, Indonesians demonstrated significantly higher anxiety and stress compared to Malaysian samples. Despite the contrasting COVID-19 situations in Malaysia and Indonesia, psychopathologies were more affected in Indonesia. Hence, our study suggests how crucial it is for mental health providers to consider promoting psychological mindedness, psychological mindfulness, and psychological flexibility to alleviate the corresponding psychopathologies among undergraduate students.